The Influence of Participative Management, Organizational Commitment, Perceived Organizational Support, and Employee Engagement on the Organizational Citizenship Behavior of Public Sector Employees - Dea Rizky Amanda Panjaitan; Yasmine Nasution (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the influence of perceived participative management, organizational commitment, and perceived organizational support on Organizational Citizenship Behavior (OCB), with employee engagement as a mediating variable. The research was conducted within a Financial Education and Training Organization in Indonesia, involving respondents comprising staff and supervisors or equivalent positions. Identified issues include a decline in the assessment index from the 2023 Service User Satisfaction Survey and a need to enhance employee behavior, particularly empathy. The research methodology employed data collection through questionnaires, which were analyzed using Lisrel 8.8 to evaluate the relationships and impacts of the studied variables. The findings reveal that participative management does not exert a direct influence on OCB; rather, its positive effect is contingent upon mediation by employee engagement. Although organizational commitment does not show a significant direct effect on OCB, it can exert an indirect influence when mediated by employee engagement. In contrast, perceived organizational support demonstrates a positive and significant effect on OCB, underscoring its critical role in fostering OCB among employees within the Financial Education and Training Organization. Employee engagement emerges as a highly influential variable, exerting a strong and significant direct impact on OCB while also mediating the indirect effects of participative management, organizational commitment, and perceived organizational support. These findings collectively emphasize the critical role of fostering employee attachment to the organization to enhance OCB.